Demodicosis Imitating Acne Vulgaris: A Case Report - Paichitrojjana A (Dove Medical Press, 2022)
Anon Paichitrojjana School of Anti-Aging and Regenerative Medicine, Mae Fah Luang University, Bangkok, 10110, ThailandCorrespondence: Anon Paichitrojjana, School of Anti-Aging and Regenerative Medicine, Mae Fah Luang University, 36/87-88 PS Tower 25Fl, Asoke Road, Sukumvit 21, Klong Toey Nua, Wattana, Bangkok, 10110, Thailand, Tel +66819343050, Email anonpaic@gmail.comAbstract: Demodicosis is caused by Demodex mite infestation and can present with a variety of clinical manifestations, including pityriasis folliculorum type, rosacea-like type, folliculitis-like type and perioral dermatitis-like type. Therefore, this skin condition is often misdiagnosed or underdiagnosed. This report presents a 19-year-old woman with a history of pityriasis folliculorum type demodicosis and successful treatment with oral ivermectin. After one year of remission, the patient began to develop a dry, itchy rash on her face for one month before multiple small edematous papules and pustules gradually appeared on both cheeks. The patient was first diagnosed as acne vulgaris and treated with doxycycline for 2 weeks, but the clinical symptoms did not show any signs of improvement. After reassessment based on clinical presentation and laboratory examination that found multiple Demodex mites from pustules and rash on both cheeks, the patient was diagnosed with folliculitis-like type demodicosis. However, this patient still had a very good response to oral ivermectin and metronidazole gel, and all clinical symptoms disappeared within 4 weeks after treatment. This is a case report of demodicosis imitating acne vulgaris and the first report demonstrating a change in clinical manifestations of demodicosis from pityriasis folliculorum type to folliculitis-like type.Keywords: Demodex mite, demodicosis, acne vulgaris, pityriasis folliculorum, folliculitis-like demodicosis